Spatial analysis on distribution of green belt to reduce impacts of climate change in Medan City, North Sumatra - Rahmawaty,; Pindi Patana,; Siti Latifah, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Medan, the capital city of North Sumatra Province, which consists of 21 sub-districts, encompasses 26.510 ha or 3.6% of the total province area. One way to reduce emissions and air pollution in urban areas is to create open green space. This study aimed to analyse and map trees in the green belt of Medan City as an effort to alleviate negative effects of climate change. Global Positioning System (GPS) was used to record the coordinate’s points of trees. The Geographic Information System (GIS) was used to analyze the distribution of green belt. Tree inventory was conducted by census method to analyze the composition and density of tree species. The results showed that most of the green belt was dominated by trees with species composition including the category of very low (84.4%). Tree density levels were dominated by very tightly category (78.1%). The Location of green belt with the highest density level was Jalan Sunggal, Medan Sunggal Sub District with a value of 1,893.75 trees/ha (very tightly). Pterocarpus indicus was the highest Importance Value Index (88.47%), followed by Switenia macrophylla (57.30%) and Oreodoxa regia (53.64%). Species diversity classified as average category (1.45). There are similarity of plant community among sampled green belt locations. The map of green belt resulted from this research could be used as one of the basis in a decision making to reduce negative effects of climate change in Medan city. As one of the largest cities in Indonesia, the existence of green belt area in Medan City is a must. Therefore, it is necessary to develop green belt area in several sub districts in Medan City.